Silver Nanoparticles in Point-of-Care Diagnostics: Enhancing Sensitivity, Selectivity, and Future Prospects - Rahayu, Martina Asti (Helium: Journal of Science and Applied Chemistry, 2025)
Silver nanoparticles (AgNPs) have emerged as indispensable nanomaterials for point-of-care (POC) medical diagnostics, due to their unique optical, electrical, and chemical properties that enhance sensor sensitivity, selectivity, and stability. This review systematically discusses the fundamental physicochemical characteristics of AgNPs, with emphasis on surface plasmon resonance (SPR) and its role in signal amplification in techniques such as surface-enhanced Raman spectroscopy (SERS), electrochemical biosensors, and immunosensors. Special attention is given to how synthesis strategies, including chemical, physical, and green, affect nanoparticle uniformity, biocompatibility, and functionalization potential. The review also compares surface modification approaches, including polymer coatings for stability, aptamer/antibody conjugation for specificity, and core–shell architectures for fluorescence enhancement, highlighting their impact on biomarker detection in complex biological matrices. By critically analyzing current challenges such as aggregation, oxidation, and nonspecific binding, the paper synthesizes recent advances in antifouling strategies, scalable production, and integration of AgNPs into portable and wearable diagnostic platforms. Unlike previous reviews, this work consolidates developments across synthesis, surface chemistry, and device engineering, and provides a forward-looking perspective on multiparametric and theragnostic applications. Overall, the paper underlines the importance of multidisciplinary collaboration to accelerate the translation of AgNPs-based sensors into clinically viable POC technologies for personalized healthcare and early disease detection.